Radiation transport in kinetic simulations and the influence of photoemission on electron current in self-sustaining discharges. (12th January 2017) - Fierro, Andrew; Moore, Chris; Scheiner, Brett; Yee, Benjamin T; Hopkins, Matthew M
Abstract: A kinetic description for electronic excitation of helium for principal quantum number n ⩽ 4 has been included into a particle-in-cell (PIC) simulation utilizing direct simulation Monte Carlo (DSMC) for electron-neutral interactions. The excited electronic levels radiate state-dependent photons with wavelengths from the extreme ultraviolet (EUV) to visible regimes. Photon wavelengths are chosen according to a Voigt distribution accounting for the natural, pressure, and Doppler broadened linewidths. This method allows for reconstruction of the emission spectrum for a non-thermalized electron energy distribution function (EEDF) and investigation of high energy photon effects on surfaces, specifically photoemission. A parallel plate discharge with a fixed field (i.e. space charge neglected) is used to investigate the effects of including photoemission for a Townsend discharge. When operating at a voltage near the self-sustaining discharge threshold, it is observed that the electron current into the anode is higher when including photoemission from the cathode than without even when accounting for self-absorption from ground state atoms. The photocurrent has been observed to account for as much as 20% of the total current from the cathode under steady-state conditions.